Natural Gas Technology - Natural Gas in the Province of Alberta, Canada - J. F. Dougherty; Anthony Folger; Howard R. Lowe; Joffre Meyer; E. G. Trostel (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1952)
The status of the natural gas industry in Alberta, Canada, is described with particular reference to the current extent of natural gas reserves and possibilities for additional development. Certain major fields are discussed as representative of the types of gas accumulations within various broad geographical divisions of the provinces. The estimation of the future performance of a gas reservoir is discussed as the basis for an estimate of the future availability of natural gas from presently known reserves. The future availability of the provincial reserves and the estimated future demand for gas within the province are described. INTRODUCTION This paper is a condensation of a detailed study of the natural gas reserves and the future availability of pipeline gas in the province of Alberta as prepared for Trans-Canada Pipe Lines Limited and presented in public hearings at Edmonton and Calgary before the Petroleum and Natural Gas Conservation Board of the Province of Alberta. The study began in October, 1950, and resulted in the preparation of five volumes of data at the expenditure of more than 20,000 man-hours. This paper is designed to afford a broad picture with detail limited to a type example of both natural ga-accumulation and future availability of gas supply. The province of Alberta has an area of 255.285 square miles which, for sake of comparison. is 8,359 square miles smaller than the state of Texas. Natural gas was first discovered in 1883 at the now abandoned Alderson well located some 20 miles southeast of the town of Princess. The first gas in commercial quantities was found at Medicine Hat in 1890. During the last 68 years. 187 localities have been discovered which are capable of gas production, and 73 per cent of these have been found since 1945. Sixty fields currently are producing gas, including 22 non-associated gas accumulations. Location of the oil and gas fields and prospects in the province of Alberta is shown in Fig. 1, together with a list of the localities of measurable gas, Fig. 1A. The estimated total provincial gas reserve as of Jan. 1, 1952, for the 104 fields estimated, is 11.7 trillion cu ft proved and probable, and for the 187 known areas capable of production is in excess of 16 trillion cu ft on a total proved, probable, and possible basis. Five fields (Pincher Creek, Leduc-Woodbend, Viking-Kinsella, Cessford and Medicine Hat) are estimated to have recoverable reserves of more than one trillion cu ft each. A sixth field, Turner Valley, was initially in this group, but its reserves have been depleted substantially. Twenty-four fields, of which the above mentioned six fields are a part, have estimated gas reserves (including the possible category) in excess of 100 billion cu ft. These 24 fields account for 79 per cent of the total provincial reserves. Comparative systemic analyses reflect that 56 per cant of Alberta's gas reserves are contained in sediments of Cretaceous age; 30 per cent in sediments of Mississippian age; 10 per cent in sediments of Devonian age; three per cent in sediments of Triassic age; and the remaining one per cent in Jurassic and Permo-Pennsylvanian sediments. It is expected that the relative importance of the Mississippian, Devonian, and Triassic sediments will be increased as exploration progresses. GENERAL GEOLOGY The western Canada basin comprises the sedimentary area between the Canadian Shield and the Rocky Mountain Front Range, the Arctic Ocean, and the International Boundary. The basin has an approximate area of 765,000 square miles and embraces parts of the provinces of Manitoba. Saskatchewan. Alberta, British Columbia and the Northwest Territories. Generalized columnar sections for the Province of Alberta are shown in Fig. 2. Substantially all of Alberta, except its northeast corner, has sedimentary cover. Sediments of all the geologic systems are represented. except those of Silurian age.